Investigating the orientation of Hafit tomb entrances in WādīʿAndām, Oman - Deadman, William M. (Proceedings of the Seminar for Arabian Studies, 2014)
This paper presents the results and analysis of a small research project exploring the orientation of Hafit tomb entrances in Wadi Andam, Oman. Measurements were taken at three sites along the course of the wadi: Fulayj in the northern mountains, Khashbah in the foothills, and ʿUyun on the plains to the south. The clear similarity between the collective tomb entrance orientation data and the annual variation in the position of the sunrise suggests that the path of the sun was of great significance to the Hafit population of Wadi Andam, and that it was recorded in their tomb architecture. Variation in the tomb entrance data between the three sites suggests that the population was nomadic and moved between areas of Wadi Andam according to season. These results are discussed in the context of the distribution of Hafit tombs and the terrain of Wadi Andam in order to explore how, where, and when this seasonal migration could have occurred. Ethnographic studies of the modern nomadic pastoralists of Oman and the UAE are examined to provide potential parallels and to obtain a better understanding of the driving force behind the Hafit seasonal nomadism. The tomb entrance orientation measurements from Wadi Andam are also presented alongside the available published data, revealing a possible east/west regional divide in the Hafit funerary architecture of the northern Oman peninsula. The results of this research suggest that the Hafit population of Wadi Andam was nomadic, and migrated from the southern plains in the summer to the mountains and foothills when the rains came in the winter, moving through the terrain along the major watercourses and building tombs on nearby elevated areas as they were needed, with entrances pointing towards the sunrise.